2008
DOI: 10.1074/jbc.m709105200
|View full text |Cite
|
Sign up to set email alerts
|

Requirement of Adaptor Protein GULP during Stabilin-2-mediated Cell Corpse Engulfment

Abstract: The prompt clearance of cells undergoing apoptosis is critical during embryonic development and normal tissue turnover, as well as during inflammation and autoimmune responses. We recently demonstrated that stabilin-2 is a phosphatidylserine receptor that mediates the clearance of apoptotic cells, thereby releasing the anti-inflammatory cytokine, transforming growth factor-␤. However, the downstream signaling components of stabilin-2-mediated phagocytosis are not known. Here, we provide evidence that the adapt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
81
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(89 citation statements)
references
References 34 publications
3
81
0
Order By: Relevance
“…43 Stabilin2-mediated uptake of apoptotic cells requires the adaptor molecule, GULP. 44 Our findings demonstrate that CD300b alone can not only tether apoptotic cells, but can mediate efferocytosis when associated with the adaptor molecule, DAP12. Importantly, our results showed that CD300b promotes phagocytosis of apoptotic cells, 45 or avb3 and CD36, 46 can cooperate to enhance efferocytosis.…”
Section: Resultsmentioning
confidence: 65%
“…43 Stabilin2-mediated uptake of apoptotic cells requires the adaptor molecule, GULP. 44 Our findings demonstrate that CD300b alone can not only tether apoptotic cells, but can mediate efferocytosis when associated with the adaptor molecule, DAP12. Importantly, our results showed that CD300b promotes phagocytosis of apoptotic cells, 45 or avb3 and CD36, 46 can cooperate to enhance efferocytosis.…”
Section: Resultsmentioning
confidence: 65%
“…Besides SR-BI, several PS-recognizing phagocytosis receptors have been identified. Kim and colleagues reported that like SR-BI, PS-bound stabilin-2 binds to GULP and transmits a signal for the induction of phagocytosis (21,35). In contrast, another PS receptor BAI1 binds to the mammalian homologue of CED-12 and transmits a signal for phagocytosis via the mammalian homologue of CED-5 and Rac1 (36).…”
Section: Resultsmentioning
confidence: 99%
“…The region covering nucleotide positions 348-1019, with the first nucleotide for the translation start codon numbered as 1, of mouse GULP cDNA placed in front of the T7 promoter was synthesized by PCR, and the GULP sequence was transcribed in vitro and processed by dicer (21). siRNA containing a sequence of green fluorescence protein was similarly generated.…”
Section: Methodsmentioning
confidence: 99%
“…12 Stabilin-2 has been reported to require the adapter protein GULP and thymosinβ 4 to engulf apoptotic cells. 19,20 Once internalized, phagolysosome maturation occurs through the action of several Rab-family GTPases eventually leading to the degradation of the ingested cell corpse. 21 'Find-me' signals Both non-professional phagocytes and resident professional phagocytes can clear dying cells under homeostatic conditions.…”
Section: Steps Involved In Clearancementioning
confidence: 99%